Pd nanoparticles supported on N-incorporated hybrid organosilica as an active and selective low-temperature phenol hydrogenation catalyst - Betsy, K. J.; Bajpai, Priyam; Lazar, Anish; Vanka, Kumar; Vinod, C. P. (ACS Applied Nano Materials, 2023)
A heterogeneous Pd-NPMO hybrid-silicacatalyst is synthesized andits application for aqueous phase selective hydrogenation of phenolto cyclohexanone at near ambient temperature (40 degrees C) and underatmospheric hydrogen pressure is demonstrated. The homogeneously distributedPd nanoparticles on N-bridged hybrid mesoporous organosilica showedremarkable activity and selectivity for cyclohexanone compared tothe unmodified Pd-SBA-15 catalyst. Control experiments strongly claimthe role of nitrogen domains in the organic framework of hybrid silicasupport in stabilizing small Pd nanoparticles and possibly modifyingthe Pd sites responsible for catalysis to activate the substrate moleculesin water. The hybrid silica catalyst was stable and reused severaltimes without any significant drop-in activity, proving the heterogeneityof the bifunctional Pd catalyst. Based on the density functional theorystudy and experimental interventions, a possible reaction mechanismfor the low-temperature phenol hydrogenation explaining the role oforganic domains in the hybrid-silica framework is proposed.
Keywords: cyclohexanone; Hybrid silica; palladium nanoparticles; Periodic mesoporous organosilica; phenol hydrogenation

Hydrogen evolution via photocatalytic reforming of biomass with palladium nanoparticles decorated g-C3N4 nanosheets - Thara, Chinnu R.; Walko, Priyanka S.; Mathew, Beena (Renewable Energy, 2024)
Fossil fuel depletion and environmental toxins have made photocatalytic H2 production of paramount significance. A novel and unique technique for producing sustainable H2 and valorizing biomass using infinite solar energy is biomass photoreformation. Nevertheless, this environmentally friendly method is usually linked to severe reaction circumstances, insufficient selectivity, and restricted biomass conversion. Here, we present a novel one-pot photoreformation technique over porous g-C3N4 nanosheets surface-modified with Pd nano- particles to convert D-glucose to H2. By stacking the g-C3N4 photocatalyst into a 2D nanosheet structure, some of its inherent drawbacks can be mitigated. Furthermore, the inclusion of noble metal nanoparticles in these g-C3N4 nanosheet structures could significantly boost existing photocatalytic activity. The majority of solar radiation is composed of visible light, which makes up 45% of it, and ultraviolet light, which makes up 5%. Therefore, our focus has been on utilizing abundant visible light to facilitate biomass reformation. After 4 h of continuous irradiation, our composite photocatalyst exhibited exceptional visible light activity; its H2 evolution was 1839.84 mu molg- 1h- 1 , or about 27 times higher than that of undoped g-C3N4 nanosheets. The effectiveness of three different Pd loadings on g-C3N4 nanosheets for glucose reforming was examined. In the quest for an improved H2 evolution visible light active photocatalyst, g-C3N4 nanosheets made at various pyrolysis temperatures loaded with optimized Pd weight percentage were also examined.
Keywords: Biomass; D -glucose; g-C 3 N 4 nanosheets; Hydrogen evolution; palladium nanoparticles; Photocatalytic reforming